A KINETIC CALCULATION METHOD OF HOMOHOPANOID MATURATION: APPLICATIONS IN THE RECONSTRUCTION OF BURIAL HISTORIES OF SEDIMENTARY BASINS - van Duin A.C.T.; Sinninghe Damste J.S.; Koopmans M.P.; van de Graaf B.; De Leeuw J.W. (My University, 1997)
Hydrous pyrolysis, performed at relatively low temperatures, of an immature marl yielded artificial maturation data on changes in homohopane isomer compositions. At higher temperatures enhanced amounts of 17α,21β(H)- and 17β,21α-hopanes over 17β,21β(H)-hopanes are observed. The amounts of 22S epimers increase relative to those of their 22R counterparts with increasing temperature. These experimental data, as well as sedimentary data on homohopane concentrations, have been reproduced using a kinetic calculation method, based on the thermodynamic stabilities determined by molecular mechanics calculation, using a full isomerization scheme rather than a single direct chiral isomerization step. We need to caution, however, that agreement between the predictions from a theoretical scheme and quantitative measurements is not an unequivocal proof for the chosen kinetic model. Good reproduction of the maturation data was obtained even for those obtained at the highest pyrolysis temperatures, at which significant destruction of hopane isomers was apparent. These results indicate that the kinetic calculation method can be used to model diagenetic and catagenetic reactions affecting biomarker ratios in sediments. Further computer simulations indicate that hopane-hopene interconversion reactions probably only have a minor influence on hopane isomer ratios.